Ozone-response mechanisms in tobacco implications of polyamine metabolism - Van Buuren, Marianne Louise (The New phytologist, 2002)
•   Polyamines have been suggested to counteract oxidative damage in plants. Here, we present a detailed analysis of polyamine accumulation and its relationship to photosynthetic parameters in two tobacco (Nicotiana tabacum) cultivars (ozone-sensitive Bel W3 and ozone-tolerant Bel B) after a single ozone pulse and after a 1-month exposure in the open air. •   Free putrescine accumulated in undamaged tissue of both cultivars, whereas putrescine conjugated to soluble and cell-wall bound components accumulated predominantly in tissue undergoing cell death in Bel W3 plants. Accumulation was caused by a redirection of the conjugation pathway, as well as by a transient increase in arginine decarboxylase and ornithine decarboxylase specific activity. This increase seemed to be regulated at post-transcriptional level. •   Measurements of chlorophyll content and fluorescence showed that, in addition to visible necrotic lesions, Bel W3 plants suffered considerable photosynthetic damage in other parts of the leaf. •   Accumulation of conjugated putrescine is part of the ozone-induced programmed cell death response in Bel W3 plants. Ozone-induced synthesis of free putrescine is not correlated with ozone-resistance in Bel B plants, which are apparently impaired in signal transduction pathways that are necessary to control the cellular redox state. However, Bel B plants are able to perceive ozone stress and to induce a series of defense mechanisms without activating hypersensitive cell death